2007
DOI: 10.1007/s00101-007-1199-4
|View full text |Cite
|
Sign up to set email alerts
|

Klinische Pharmakologie

Abstract: The rule of three describes three steps which are needed for an optimal control of postoperative nausea and vomiting (PONV). Firstly, patients at high risk of PONV need to be identified. Knowledge about predictive factors may help to identify patients who may best profit from prophylaxis and those where prophylaxis is not worthwhile since the baseline risk is too low. Secondly, for high-risk patients a low emetogenic anaesthesia technique should be chosen, and thirdly, these patients should additionally receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“… 1 , 2 , 3 , 4 , 5 , 6 Although some believe that the main causative factor for PONV is the anesthetic materials, several studies demonstrated effect of a wide range of factors such as age, sex, the time between last meal and operation, the history of PONV, the anesthetic methods and the type of surgical procedures on PONV. 2 , 4 , 5 Since long hospital stay, poor patient satisfaction from the medical team and increased treatment cost are the most morbidities associated with postoperative nausea and vomiting, its prevention and treatment pose a significant challenge in the modern medicine. 2 , 5 , 6 , 7 Other complications of PONV include electrolyte disorders, increased pain, hypertension and probably elevated risk of pulmonary aspiration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 , 2 , 3 , 4 , 5 , 6 Although some believe that the main causative factor for PONV is the anesthetic materials, several studies demonstrated effect of a wide range of factors such as age, sex, the time between last meal and operation, the history of PONV, the anesthetic methods and the type of surgical procedures on PONV. 2 , 4 , 5 Since long hospital stay, poor patient satisfaction from the medical team and increased treatment cost are the most morbidities associated with postoperative nausea and vomiting, its prevention and treatment pose a significant challenge in the modern medicine. 2 , 5 , 6 , 7 Other complications of PONV include electrolyte disorders, increased pain, hypertension and probably elevated risk of pulmonary aspiration.…”
Section: Introductionmentioning
confidence: 99%
“…2 , 5 , 6 , 7 Other complications of PONV include electrolyte disorders, increased pain, hypertension and probably elevated risk of pulmonary aspiration. 2 , 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the investigations of Apfel and others, serotonin antagonists are primarily used as second- or third-line drugs in preventing or treating PONV [32,40]. The relative expensiveness of these drugs may limit general use, considering increasing economic constraints in most health care systems [40,41]. …”
Section: Discussionmentioning
confidence: 99%
“…Patients at high risk for PONV should be provided with a combination prophylaxis and as many potential risk factors as possible should be eliminated, whereas patients with a low risk of PONV might be supported with one antiemetic or managed with a "wait-and-see" strategy. 26 This means that patients with a very low risk of PONV should not be exposed to the potential side effects of antiemetics and should only be treated with antiemetics if PONV really occurs.…”
Section: How To Identify Patients At Riskmentioning
confidence: 99%